Transportation Planning Model - Jan Celko; Marek Drliciak; Andrea Gavulova (Communications - Scientific letters of the University of Zilina, 2007)
The traffic congestion represents a very important problem of the cities at present. The results are a frustration of motorists; longer travel times; an increase of accidents and fuel consumption and negative effect to the environment. The transport relations modeling by exact analysis of the real traffic state is a complex solution. This solution enables a determination of the future demands depending on traffic forecast. The article presents the main process of transport modeling based on four-step solution. This process is completed by its practical using in the town of Zlina. The transport relation analyses, the modal split and traffic distribution are described. The focus of the article is approaching the transport-modeling dilemma.